Beta-receptor desensitization after a multistage ultralong distance exercise in the desert?. (14th October 2021) - Chague, F; Carre, F; Gudjoncik, A; Richard, C; Compagnon, F; Ganancia, O; Pasquereau, V; Zeller, M; Cottin, Y
Abstract: Background: Although cardiac function has been largely investigated during ultra-endurance exercise, few studies addressed to multi-stage endurance race. Methods: Serial echocardiographic assessment of cardiac function was performed in male healthy subjects during the 2014 Marathon des Sables before the race (T1), at the second (T2) and fifth (T3) arrival (236 km) then after 48h recovery. Analysis were performed by 2 sonographers blind for the results of the other and the time of measure. Results: Among the 20 athletes, 18 completed the study (mean age 42.4, median 42). RR intervals and (Left ventricular End Diastolic Volume (Simpson) (LVEDV) changed during the race and were correlated (r2 = 0.539, p<0.001); afterload approched by Left Ventricular Meridional Wall Stress (LVMWS) did not change. LV Global Longitudinal Peak Strain (PS) and subepicardial (Epi) PS did not vary. Subendocardial (Endo) LV.PS was lower at T2 /T1, concomitant to a (non-significant) drop in LVEDV; LV strain rate (SR) was lower at T4. RR and LVEDV were higher at T3 than at T2, and higher at T4 compared to T1 and T2. As preload conditions changed during the race, we studied the response of PS and SR to the change in preload (Starling mechanism). EndoPS/LVEDV, LVPS/LVEDV and SR/LVEDV did not change during the race but were lower after recovery. Conclusions: 48h after a multistage ultralong duration exercise, we observed a drop in heart rate and contractility response to preload. The evolution of these parameters could be explained by a beta-receptors desensitization. These data need to be confirmed by other studies. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): CHU Dijon Bourgogne ARS Bourgogne Franche Comté